Implementasi Program Green Campus melalui Penanaman dan Penamaan Pohon Pelindung sebagai Upaya Penguatan Kesadaran Lingkungan Mahasiswa - Dede Margo Irianto; Yeni Yuniarti; Tita Mulyati; Yunus Abidin; Yusuf Tri Herlambang; Rahman Wahid; Iim Siti Karimah; Yadi Suryadi (CV. Ksatria Siliwangi, 2024)
This community service program aims to develop community environmental literacy through inorganic waste management activities based on waste banks. Waste Bank is one of the effective solutions in overcoming the accumulation of inorganic waste in the community and manage it into something more useful. There are benefits that can be generated from the management of inorganic waste. In addition, this community service program is encouraged by the low level of community environmental literacy which is shown by the lack of community skills in managing inorganic waste. The method used in the community service program is carried out using the 7D model method with preliminary survey methods, training, mentoring, evaluation, and discussion. The results of community service activities carried out in Pasir Biru Village, Cibiru District, Bandung City went according to plan and obtained a fairly good level of satisfaction from partners.